2004
DOI: 10.1086/423147
|View full text |Cite
|
Sign up to set email alerts
|

A Predominantly Neolithic Origin for Y-Chromosomal DNA Variation in North Africa

Abstract: We have typed 275 men from five populations in Algeria, Tunisia, and Egypt with a set of 119 binary markers and 15 microsatellites from the Y chromosome, and we have analyzed the results together with published data from Moroccan populations. North African Y-chromosomal diversity is geographically structured and fits the pattern expected under an isolation-by-distance model. Autocorrelation analyses reveal an east-west cline of genetic variation that extends into the Middle East and is compatible with a hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
174
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(196 citation statements)
references
References 32 publications
(41 reference statements)
18
174
4
Order By: Relevance
“…Haplogroup E-DYS271, which accounts for 470% of the Y chromosomes in most of the populations south of the Sahara, is found on an average at a frequency of 2-3% in Northern Africa, whereas haplogroups J-M304, E-M81, and E-M78, which on the whole account for 50-90% of the northern African male-specific region of the Y chromosome (MSY) gene pool, have been only rarely observed in west/central sub-Saharan Africa. [12][13][14][15][16][17][18][19][20][21][22][23][24][25] A group of chromosomes of potential interest to past trans-Saharan connections is the paragroup R1b1* (R-P25*). Cruciani et al 18 found this paragroup (at that time defined as haplogroup 117, or R-M173*(xSRY 10831 , M18, M73, M269)) to be present at high frequencies (up to 95%) in populations from northern Cameroon.…”
Section: Introductionmentioning
confidence: 99%
“…Haplogroup E-DYS271, which accounts for 470% of the Y chromosomes in most of the populations south of the Sahara, is found on an average at a frequency of 2-3% in Northern Africa, whereas haplogroups J-M304, E-M81, and E-M78, which on the whole account for 50-90% of the northern African male-specific region of the Y chromosome (MSY) gene pool, have been only rarely observed in west/central sub-Saharan Africa. [12][13][14][15][16][17][18][19][20][21][22][23][24][25] A group of chromosomes of potential interest to past trans-Saharan connections is the paragroup R1b1* (R-P25*). Cruciani et al 18 found this paragroup (at that time defined as haplogroup 117, or R-M173*(xSRY 10831 , M18, M73, M269)) to be present at high frequencies (up to 95%) in populations from northern Cameroon.…”
Section: Introductionmentioning
confidence: 99%
“…Curiously, TTan also presents the highest frequency (33.3%) of West Eurasian R1b lineages whereas TGor presents only 5.6% of lineage K* (xO,P), and TGos presents none. There were no instances of the Eurasian J haplogroup in the Tuareg, which is otherwise frequent in North Africa (an average of 20%; see Arredi et al 45 ), and attains the highest frequency in the Middle East (around 50%; see Semino et al) 46 .…”
Section: Y Chromosome Pool In Tuaregmentioning
confidence: 93%
“…This haplogroup reaches a mean frequency of 42% in North Africa, decreasing in frequency from 76% in Morocco to B10% in Egypt. 45 Arredi et al 45 dated this haplogroup in North Africa from 2800 to 9800 YBP, associating its expansion with the Neolithic demic diffusion of Afro-Asiatic-speaking pastoralists from the Middle East.…”
Section: Y Chromosome Pool In Tuaregmentioning
confidence: 99%
“…27,38,[42][43][44][45]39 Previous investigations have found some of these haplogroups, including J1-M267 and J2-M172, to illustrate patterns of distributions that reflect the spread of agriculture and domestication from the Fertile Crescent, 37,45 and recently, the distribution of R1b1b-M269 haplotypes across the Near East and Europe has been proposed to be best explained by a Neolithic dispersal. 44 Of particular prominence in Armenia are haplogroups R1b-M343 and J2-M172, which are detected in Ararat Valley, Gardman and Lake Van at frequencies higher than those observed in any of the Near Eastern populations analyzed in this study.…”
Section: Genetic Support For Neolithic Origins Of the Armenian Populamentioning
confidence: 99%